Mechanistic Pathways for Peptidoglycan O-Acetylation and De-O-Acetylation - Sychantha, David; Brott, Ashley S.; Jones, Carys S.; Clarke, Anthony J. (Frontiers in Microbiology, 2018)
The post-synthetic O-acetylation of the essential component of bacterial cell walls, peptidoglycan, is performed by many pathogenic bacteria to help them evade the lytic action of innate immunity responses. Occurring at the C-6 hydroxyl of N-acetylmuramoyl residues, this modification to the glycan backbone of peptidoglycan sterically blocks the activity of lysozymes. As such, the enzyme responsible for this modification in Gram-positive bacteria is recognized as a virulence factor. With negative bacteria, the O-acetylation of peptidoglycan provides a means of control of their autolysins at the substrate level. In this review, we discuss the pathways for peptidoglycan O-acetylation and de-O-acetylation and the structure and function relationship of the O-acetyltransferases and O-acetylesterases that catalyze these reactions. The current understanding of their mechanisms of action is presented and the prospects of targeting these systems for the development of novel therapeutics are explored.